1996
DOI: 10.1074/jbc.271.12.7019
|View full text |Cite
|
Sign up to set email alerts
|

Shedding of the Lymphocyte L-Selectin Adhesion Molecule Is Inhibited by a Hydroxamic Acid-based Protease Inhibitor

Abstract: Expression of the L-selectin adhesion molecule can be rapidly down-modulated by regulated proteolysis at a membrane-proximal site. The L-selectin secretase has remained undefined, and the secretase activity is resistant to a broad panel of common protease inhibitors. We have developed an L-selectin-alkaline phosphatase reporter, consisting of the ectodomain of human placental alkaline phosphatase fused to the membrane-proximal cleavage, transmembrane, and cytoplasmic domains of L-selectin, to aid in the screen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
102
0

Year Published

1997
1997
2013
2013

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 139 publications
(104 citation statements)
references
References 34 publications
2
102
0
Order By: Relevance
“…TGF-oc, M-CSF, FasL, etc. (Crowe et al, 1995;Kayagaki et al, 1995;Mullberg et al, 1995;Bennett et al, 1996;Couet et al, 1996;Drummond and Gearing, 1996;Feehan et al, 1996). Another parameter was obtained by gel filtration of CM revealing a peak of activity with a molecular mass of 89 kDa.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…TGF-oc, M-CSF, FasL, etc. (Crowe et al, 1995;Kayagaki et al, 1995;Mullberg et al, 1995;Bennett et al, 1996;Couet et al, 1996;Drummond and Gearing, 1996;Feehan et al, 1996). Another parameter was obtained by gel filtration of CM revealing a peak of activity with a molecular mass of 89 kDa.…”
Section: Resultsmentioning
confidence: 99%
“…MMPIs were originally designed to reduce excessive MMP activity due to an imbalance of MMPs and their natural inhibitors (TIMPs). However, synthetic MMPIs also inhibit shedding of TNF-ox from its membrane spanning precursor (Gearing et al, 1994(Gearing et al, , 1995 and of other cytokines: TGF-oc, FasL, C) Cancer Research Campaign 1998 IL-6 receptor, stem cell factor, M-CSF, TNF-oc receptors, Lselectin and thyrotropin receptor ectodomain (Crowe et al, 1995;Kayagaki et al, 1995;Mullberg et al, 1995;Bennett et al, 1996;Couet et al, 1996;Drummond and Gearing, 1996;Feehan et al, 1996). Therefore, inhibition of release of cytokines that play a role in tumour development represents an alternative or additional mechanism of action of MMPIs.…”
Section: Resultsmentioning
confidence: 99%
“…The MEK1 inhibitor U0126 and sequencing grade modified trypsin were purchased from Promega (San Luis Obispo, CA). TAPI-1, an inhibitor of metalloproteases, including TACE, was a gift from Dr. T. K. Kishimoto (Boehringer Ingelheim) (30,39). Phenanthroline, another metalloprotease/TACE inhibitor, was purchased from Sigma (47).…”
Section: Methodsmentioning
confidence: 99%
“…The detection of both the mature 100-kDa TACE and 20-kDa SPRACT under these conditions suggests that SPRACT is unlikely to be generated by autolysis during sample preparation. Previous studies (30,39) have shown that the metalloprotease inhibitor TAPI-1 inhibits the cleavage activity of TACE. Inclusion of TAPI-1 (10 M) and phenanthroline (10 mM) in the cell lysis buffer and throughout subsequent washes in immunoprecipitation did not decrease the level of SPRACT in such experiments (data not shown).…”
Section: Tace Is Phosphorylated In Response Tomentioning
confidence: 96%
“…Staurosporine, wortmannin, H89, KT5823, genistein, and K252b were purchased from Alexia (San Diego, CA); Gö-7874, Ro-31-8220, bisindolylmaleimide 1, rottlerin, and calphostin C were purchased from Calbiochem (San Diego, CA). KD-IX-73-4, a hydroxamic acid-based metalloprotease inhibitor, has previously been shown to block activation-induced L-selectin shedding [13,18]. All kinase inhibitors and KD-IX-73-4 were dissolved in dimethyl sulfoxide (DMSO) and diluted at least 1000-fold for all whole-cell assays.…”
Section: Reagentsmentioning
confidence: 99%